Toward in-vivo cancer detection: X-ray scattering on thick phantom samples - Kubytskyi, Viacheslav; Khonkhodzhaev, Masroor; Tanaka, Aika; Nguyen, Audrey; Lazarev, Alexander; Aram, Byron; Rogers, Keith; Mourokh, Lev; Lazarev, Pavel (MDPI, 2025)
As the number of new breast cancer cases grows around the world, there is an unmet need for fast, accurate, and low-cost methods of early cancer detection. It was previously shown that X-ray scattering on lipid molecules can provide the necessary structural biomarker. However, these measurements were performed on small ex vivo samples, and to ensure the progress to in vivo diagnostics, the approach should be extended to larger tissues. We use the phantom fat samples to establish such a procedure. In the obtained X-ray scattering patterns, we observe the characteristic features for the inter-fatty-acid molecular distance. The large size of the samples led to the peak broadening; however, the features remain visible up to 10 cm in thickness. The experimental data are in excellent agreement with the Monte Carlo simulations based on the form factors obtained from the small samples. Our results usher the way for the in vivo monitoring of the structural biomarkers of breast cancer.
This article belongs to the Section Photochemistry
Keywords: 32 Biomedical and Clinical Sciences; 34 Chemical Sciences; 3211 Oncology and Carcinogenesis; Bioengineering; Women's Health; Breast Cancer; Cancer; Prevention; 4.1 Discovery and preclinical testing of markers and technologies; cancer detection; X-ray scattering; Monte Carlo simulations; structural biomarkers; lipid molecules